Tax Avoidance, Tunneling, Political Connection, dan Nilai Perusahaan: Penyajian Secara Simultan - Annisa Rahma; Abdul Rahman (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2026)
This study aims to provide an empirical evidence of about is the effectof tax avoidance on tunneling, tunneling moderate tax avoidance onfirm value and political connection to moderate the effect of taxavoidance on firm value. The population in this study are all nonfinancialcompanieslistedinIndonesiaStockExchange2020-2024.The sampleofthisresearch is 86 non-financial sector companies listed onIndonesia Stock Exchange 2020-2024. collection method usingpurposive sampling technique. were selected as a sample of the total286 observations this study. The method of analysis in this study usingregression analysis two stage last square. The results of this study indicate that: 1) Tax Avoidance has positiveand significant effect on tunneling using OREC and NOREC1 proxies. 2)tunneling that moderates tax avoidance does not affect the firm value.3) political connection that moderates tax avoidance does not affectthe firm value